Relevance of molecular testing in patients with a family history of sudden death. (July 2017) - Kauferstein, Silke; Herz, Nadine; Scheiper, Stefanie; Biel, Stephanie; Jenewein, Tina; Kunis, Malte; Erkapic, Damir; Beckmann, Britt-Maria; Neumann, Thomas
Highlights: In the present study we underscore the importance of postmortem genetic testing in cases of SUD. Management of such cases requires a multidisciplinary approach. Forensic pathologists are here important partners. To benefit from of such investigations, internationally agreed recommendations are needed. Abstract: Sudden cardiac death (SCD) is a major cause of death in industrial countries. Although SCD occurs mainly in adults, it may also affect young persons, where genetic cardiac disorders comprise at least half of these cases. This includes primary arrhythmogenic disorders such as long QT syndrome and inherited cardiomyopathies. However, in many cases, postmortem examinations provide no conclusive results explaining the cause of death. Since family members of the deceased may eventually have inherited the same disease, they are at risk of SCD. In the present study, 28 patients with a family history of sudden unexplained death (SUD), of survived cardiac arrest and with a clinical diagnosis of an inherited cardiac disease were screened using phenotype-guided molecular analysis of genes associated with arrhythmogenic cardiac diseases. In 64% of the cases, gene variants with potentially pathogenic cardiac effects were detected suggesting that an arrhythmia syndrome may have caused the death of the deceased family member. Therefore, we recommend that relatives of SUD victims should undergo extended cardiac examination and, depending on the clinical diagnosis, a targeted genetic analysis should follow, which is crucial to identify family members at risk.